Autoregulation of Escherichia coli purR requires two control sites downstream of the promoter. - Rolfes, R J (1990)
The expression of Escherichia coli purR, which encodes the pur regulon repressor protein, is autoregulated. Autoregulation at the level of transcription requires two operator sites, designated purRo1 and purRo2 (O1 and O2). Operator O1 is in the region of DNA between the transcription start site and the site for translation initiation, and O2 is in the protein-coding region. The repressor protein binds noncooperatively to O1 with a sixfold-higher affinity than to O2, and saturation of O1 by the repressor precedes saturation of O2. Both O1 and O2 function in the two- to threefold autoregulation in vivo, as determined by measurement of beta-galactosidase and mRNA from purR-lacZ translational fusions. Of all the genes thus far known to be regulated by the Pur repressor, only purR employs a two-operator mechanism.